Influência do anticoagulante na obtenção e criopreservação do plasma rico em plaquetas (PCR) em equinos e muares - Ana Luisa Soares de Miranda (2016)
Platelet-Rich Plasma (PRP) is a biological product often used to promote tissue repair, due to its composition of growth factors. The aim of this study was to compare the viability of platelet cryopreservation on two species, horses and mules, and the influence of two different anticoagulants dextrose citrate (ACD) and sodium citrate (SC). Eight animals of each species were used, with two replicas each. PRP was obtained after single centrifugation at 131 g in eight minutes. Samples were frozen in liquid nitrogen after exposure to a controlled cooling rate. A solution of glucose and 3% DMSO was used as a cryoprotectant. Blood analysis were performed on hematologic analyzer, Neubauer chamber and morphology was evaluated through optical microscopy of phase inversion. Platelet concentration on PRP when compared to total blood samples were 1,42 times in horses and 2,00 in mules, using ACD; and 1,39 times in horses and 2,69 times in mules using SC. The protocol was more efficient in concentrating mules platelets when compared to horses, although both species cryopreservation had similar quality. There was a significant increase of cells in activated status after cryopreservation, despite the species or anticoagulant employed. Platelet count on ACD and SC, on total blood, was more truthful in ACD and SC when compared to EDTA, in order to establish PRP parameters. Based upon the negative effects of leukocytes on PRP, SC was more efficient in reducing total leukocyte count when compared to ACD on both species. Due to the fact that there were no significant differences between cryopreserved PRP and the anticoagulants employed (especially regarding morphology parameters of platelets), it is suggested that SC was a better anticoagulant to obtain PRP on both mules and horses. Clinical trials should be performed, especially in mules, due to its hematological distinctive features when compared to horses.